(3JMaI GdeMJGL aj Yde GdJYOjd hGdCRjGLs - (3YHO GdQMef GdaGSjs
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdCadGc GdOGFQI hHYO , aGYde Efi deG CQOJ GdTQhY ai af Yde GdJYOjd hGdCNP ajg , hbaJ Ydi HYV GdCRjGL GdJi CdagG RchW s
(3BNQgG (B:s
(3Ke CONd HGdeQcR hHGdMUI GdeYOdjf ai LOGhd GdYQV dYWGQO HGdeQcR ai GdCYdi hHGdMUI ai GdCSad eeG ELJeYG Ydjg gh YQV GdchGcH GdeWdhH GfJgi QSGdI aLGAJ HMeO Gddg LeYI GdahGFO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B3s
(3HChdgG GdQSGdI Jedc dYdi GdNTGH GdOejGWi Gdadci SfI (B1239 (3g`s
(3HgG fXGe GdJYbjHIs
(3QSGdI LGeYI Ydi RjL RchW (B_ (3eQJHI Ydi KeGfjI CHhGHhUGMH GdRjL gh RchWh(B" (3hchW (B" (3GdJYHQGfi GdCfOdSis
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs